Gender equity and COVID-19 vaccine policies for pregnant people: a global analysis - Eleonor Zavala; Elizabeth Doggett; Andrew Nicklin; Ruth A. Karron; Ruth R. Faden (International Journal for Equity in Health)
Abstract Background Despite increasing vaccine availability and evidence and expert recommendations to support administration, some countries maintained restrictive policies regarding COVID-19 vaccination in pregnancy throughout the pandemic. This global analysis explores the role of gender equity, country income level, and vaccine availability in predicting national policies on COVID-19 vaccine administration in pregnancy. Methods Policies were collected from May 2021 to January 2023 from 224 countries/territories using publicly available information posted on national public health authority web pages. Policies were categorized into 6 types, representing different levels of permissiveness, from recommended for some or all to not recommended, and changes in national policies were captured over time. Outcomes were defined as: 1) prevalence of restrictive policies at a specific time point; 2) country-level change from restrictive policy/no position at an earlier time point to a permissive policy at a later timepoint. Simple and multivariable logistic regressions were performed to explore the association between the outcomes and potential policy predictors, including income level, mRNA vaccine availability, and the Global Gender Gap Index (GGGI). Results Complete cross-sectional data were available for 114 countries as of June 2021, 137 countries as of October 2021, and 142 countries as of March 2022. The number of maternal immunization policies increased and became steadily more permissive between 2021 and 2022. Availability of mRNA vaccines and higher income level were associated with reduced odds of a restrictive policy at the 2021 timepoints, and higher GGGI scores were associated with reduced odds of restrictive policies at all timepoints. After adjusting for income level and mRNA vaccine availability, higher GGGI scores reduced the relative odds of a restrictive COVID-19 vaccine policy by 10% (aOR: 0.90, 95CI: 0.81, 0.99) in October 2021 and 14% (aOR: 0.86, 95%CI: 0.76, 0.97) in March 2021. Higher GGGI scores were also associated with increased odds of a policy switch from restrictive/no position in June 2021 to permissive in October 2021 (aOR: 1.12, 95%CI: 1.00, 1.24). Conclusions Gender inequity was associated with greater odds of a restrictive policy for use of COVID-19 vaccines in pregnancy, suggesting that gender biases may influence fair policymaking for pregnant people in pandemic preparedness and response.